TccP4: a novel effector identified in the Escherichia albertii strain 1551-2 required for attaching and effacing lesion formation on infected Nck-null cells - Iranildo do A. Fernandes; Tadasuke Ooka; Daiany R. P. de Lira; Fernando H. Martins; Henrique Orsi; Nina Jones; Waldir P. Elias; Tetsuya Hayashi; Tânia A. T. Gomes; Rodrigo T. Hernandes (Microbiology Spectrum)
ABSTRACT Escherichia albertii is a pathogen that causes sporadic cases and outbreaks of diarrhea. The main virulence feature of this bacterium is the attaching and effacing (AE) lesion formation on infected intestinal epithelial cells, which is characterized by the formation of pedestal-like structures that are rich in F-actin. The Brazilian E. albertii 1551-2 strain can recruit F-actin using both the Nck-dependent and the Nck-independent pathways, the latter of which uses an adaptor protein named Tir-cytoskeleton coupling protein (TccP/EspFU). Genome analyses of the 1551-2 strain unveiled the existence of a gene encoding a putative novel TccP subtype in addition to a gene encoding for the TccP3 subtype. Amino-acid sequence comparison with known TccP subtypes (TccP/EspFU, TccP2, and TccP3) confirmed that the protein represents a novel TccP subtype—named here TccP4. Lack of TccP4 led to an approximately 96% reduction in the ability of the tccP3 deletion mutant of strain 1551-2 to induce the F-actin-rich pedestals formation in the infected Nck-null mouse embryonic fibroblasts (MEF) cells. The tccP4 gene was distributed widely in E. albertii, including the strains first separated from other E. albertii strains, suggesting that this gene was acquired at a very early stage during the diversification of E. albertii. The highly variable genetic organization of the tccP4-containing regions and the presence of various mobile genetic elements in this region may explain the lack of tccP4 in E. albertii strains belonging to various lineages.IMPORTANCEE. albertii, one of the new members of the genus Escherichia, is a diarrheagenic pathogen. The main characteristic of its pathogenicity is the formation of attaching and effacing (AE) lesions on the surface of infected epithelial cells. Here we identified a novel subtype of the TccP type 3 secretion system (T3SS) effector family (termed TccP4), which is required for the recruitment of F-actin during the AE lesion formation in infected host cells by the E. albertii 1551-2 strain. We also revealed that TccP4 is unique to E. albertii and widely distributed in this species, suggesting that the tccP4 gene was acquired at a very early stage during the diversification process of E. albertii. These findings expand our understanding of the function and diversity of this important T3SS effector family.